Sufficient conditions for the convergence of a class of rational recursive sequences - Dang, Vu Giang (H. : ĐHQGHN, 2017)
We study the convergence of positive recursive sequence Zn + 1 = / ( x n , i n_ i). Here f ( x , y ) is a positive continuous function of two variables.